2014
DOI: 10.1055/s-0034-1376977
|View full text |Cite
|
Sign up to set email alerts
|

Formononetin Inhibits Migration and Invasion of MDA-MB-231 and 4T1 Breast Cancer Cells by Suppressing MMP-2 and MMP-9 Through PI3K/AKT Signaling Pathways

Abstract: into the blood or lymphatic vessels. The help of matrix metalloproteinases (MMPs) is required for extravasation out of the vessel, leading to the movement of cancer cells to the target tissue. Among all MMPs, MMP-2 and MMP-9, known as key enzymes in the degradation of type IV collagen, are overexpressed in breast cancer cells [ 5 , 6 ] and their elevated expression has been associated with poor prognosis [ 7 ]. Thus, MMPs could work as pivotal targets for suppressing breast cancer invasion and metastasis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
128
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(134 citation statements)
references
References 12 publications
6
128
0
Order By: Relevance
“…In addition, MMP‐2 and MMP‐9 serve as important downstream effectors of AKT 10, 23, 24 and are involved in cell motility and VM formation 10, 26. Therefore, the hypothesis that Rictor regulates VM via the AKT‐MMP‐2/9 pathway is reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MMP‐2 and MMP‐9 serve as important downstream effectors of AKT 10, 23, 24 and are involved in cell motility and VM formation 10, 26. Therefore, the hypothesis that Rictor regulates VM via the AKT‐MMP‐2/9 pathway is reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 has been considered as a potential downstream signal molecule of the Akt pathway. Some potential anticancer agents such as formononetin and piceatannol were shown to inhibit breast cancer cell invasion by suppressing MMP-9 through blocking the Akt pathway 47,48. Moreover, the activation of Akt axis is also emerging as a central feature of EMT 49.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been demonstrated that AKT signaling is involved in regulating the expression of a number of cell cycle-related proteins and MMPs (9,31,32). Therefore, the activity of AKT signaling after treatment with PDGF-BB with or without formononetin was evaluated in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…It has been well established that MMP2 and MMP9 play key roles in the regulation of cell migration (9). Therefore, the protein expression levels of MMP2 and MMP9 were determined in the VSMCs in each group.…”
Section: Formononetin Suppressed Pdgf-bb-induced Upregulation Of Mmp2mentioning
confidence: 99%
See 1 more Smart Citation